2014 iAREA campaign on aerosol in Spitsbergen – Part 1: Study of physical and chemical properties. (September 2016) - Lisok, J.; Markowicz, K.M.; Ritter, C.; Makuch, P.; Petelski, T.; Chilinski, M.; Kaminski, J.W.; Becagli, S.; Traversi, R.; Udisti, R.; Rozwadowska, A.; Jefimow, M.; et al.
Abstract: This paper presents the results of measurements of aerosol physical and chemical properties during iAREA2014 campaign that took place on Svalbard between 15th of Mar and 4th of May 2014. With respect to field area, the experiment consisted of two sites: Ny–Ålesund (78°55′N, 11°56′E) and Longyearbyen (78°13′N, 15°33′E) with further integration of Aerosol Robotic Network (AERONET) station in Hornsund (77°00′N, 15°33′E). The subject of this study is to investigate the in–situ, passive and active remote sensing observations as well as numerical simulations to describe the temporal variability of aerosol single–scattering properties during spring season on Spitsbergen. The retrieval of the data indicates several event days with enhanced single–scattering properties due to the existence of sulphate and additional sea–salt load in the atmosphere which is possibly caused by relatively high wind speed. Optical results were confirmed by numerical simulations made by the GEM–AQ model and by chemical observations that indicated up to 45% contribution of the sea–salt to a PM10 total aerosol mass concentration. An agreement between the in-situ optical and microphysical properties was found, namely: the positive correlation between aerosol scattering coefficient measured by the nephelometer and effective radius obtained from laser aerosol spectrometer as well as negative correlation between aerosol scattering coefficient and the Ångstrom exponent indicated that slightly larger particles dominated during special events. The in–situ surface observations do not show any significant enhancement of the absorption coefficient as well as the black carbon concentration which might occur during spring. All of extensive single–scattering properties indicate a diurnal cycle in Longyearbyen, where 21:00–5:00 data stays at the background level, however increasing during the day by the factor of 3–4. It is considered to be highly connected with local emissions originating in combustion, traffic and harbour activities. On the other hand, no daily fluctuations in Ny–Ålesund are observed. Mean values in Ny–Ålesund are equal to 8.2, 0.8 Mm −1 and 103 ng/m 3 for scattering, absorption coefficients and black carbon concentration; however in Longyearbyen (only data from 21:00–05:00 UTC) they reach 7.9, 0.6 Mm −1 as well as 83 ng/m 3 respectively. Overall, the spring 2014 was considerably clean and sea–salt was the major aerosol component. Highlights: Complex studies on aerosol properties during spring on Spitsbergen are presented. In-situ, remote sensing instruments and model results are included in the campaign. Scattering properties were found to be correlated with wind speed. Some sea-spray advections are detected and described in detail. Spring 2014 seems to be relatively clean with only a small load of Arctic Haze events.